Mass Spectrometry-Based Targeted Serum Monomethylated Ribonucleosides Profiling for Early Detection of Breast Cancer - Fang, Zhihao; Hu, Yiqiu; Chen, Jiani; Xu, Kailun; Wang, Kailai; Zheng, Shu; Guo, Cheng (Frontiers in Molecular Biosciences, 2021)
RNA methylation plays a significant regulatory role in various of physiological activities and it has gradually become a hotspot of epigenetics in the past decade. 2′-O-methyladenosine (Am), 2′-O-methylguanosine (Gm), 2′-O-methylcytidine (Cm), 2′-O-methyluridine (Um), N6-methyladenosine (m6A), N1-methylguanosine (m1G), 5-methylcytidine (m5C), and 5-methyluridine (m5U) are representative 2′-O-methylation and base-methylation modified epigenetic marks of RNA. Abnormal levels of these ribonucleosides were found to be related to various diseases including cancer. Serum is an important source of biofluid for the discovery of biomarkers, and novel tumor biomarkers can be explored by measuring these ribonucleoside modifications in human serum. Herein, we developed and applied a hydrophilic interaction liquid chromatography tandem mass spectrometry (HILIC-MS/MS) method to determine the content of monomethylated ribonucleosides in human serum. The developed method enabled sensitive and accurate determination of these monomethylated ribonucleosides. By applying this robust method, we demonstrated the presence of Gm and Um in human serum for the first time, and we successfully quantified m6A, Gm, m1G, Cm, Um and m5U in serum samples collected from 61 patients with breast cancer and 69 healthy controls. We discovered that the levels of Gm, m1G, Cm, Um and m5U in serum were all significantly decreased in breast cancer patients whereas m6A was increased. We performed receiver operator characteristic (ROC) curve analysis, and obtained highest area under curve (AUC) value when combining these six monomethylated ribonucleosides together. These results suggest that m6A, Gm, m1G, Cm, Um and m5U might have great potential to be novel biomarkers for detection of breast cancer in the early stage. In addition, this study may stimulate future investigations about the regulatory roles of monomethylated ribonucleosides on the initiation and development of breast cancer.